Risk factors for early mortality and severe intraventricular hemorrhage in extremely preterm infants with gestational age <28 weeks: a retrospective case-control study - Wu, Ziqi; Zhao, Yimeng; Tian, Ruifeng; Peng, Sicong; Liu, Qin; Xia, Shiwen; Zhang, Yi (Frontiers in Pediatrics, 2026)
IntroductionExtremely premature infants (EPIs) are at significant risk for early mortality and severe intraventricular hemorrhage. This study aimed to investigate the risk factors associated with early mortality and severe intraventricular hemorrhage in EPIs with a gestational age of less than 28 weeks and to evaluate the predictive value of these risk factors in determining adverse outcomes.MethodsA retrospective analysis was conducted on clinical data from EPIs admitted to the Neonatal Intensive Care Unit at Maternal and Child Health Hospital of Hubei Province between January 2019 and December 2024. Infants were categorized into two groups based on their early outcomes: an adverse outcome group (n = 110) and a favorable outcome group (n = 183). Binary logistic regression analysis was used to identify high-risk factors for adverse outcomes in EPIs, and receiver operating characteristic (ROC) curve analysis was performed to assess the predictive value of these factors.ResultsThis study revealed that the maximum vasoactive-inotropic score (Max VIS) (OR: 1.136, 95% CI: 1.070, 1.216) and middle cerebral artery resistance index (MCA-RI) (OR: 450.489, 95%CI: 36.163, 5,611.780) and vaginal delivery (OR: 3.684, 95%CI: 2.005, 6.768) were independent risk factors for adverse outcomes in EPIs, while gestational age was a protective factor (OR: 0.568, 95% CI: 0.415, 0.778). ROC curve analysis indicated that Max VIS > 9.5, MCA-RI > 0.81, vaginal delivery, and small gestational age had predictive value for adverse outcomes in EPIs (P < 0.05), with area under the curves (AUC) of 0.680 (95% CI: 0.615, 0.745), 0.693 (95%CI: 0.628, 0.758), 0.653 (95% CI: 0.588, 0.718), and 0.660 (95% CI: 0.275, 0.404), respectively. The combination of all four factors yielded the highest predictive performance, with an AUC of 0.833 (95%CI: 0.783, 0.883), sensitivity of 72.7%, and specificity of 81.4%.ConclusionElevated Max VIS, increased MCA-RI, vaginal delivery, and small gestational age are independent risk factors for early mortality and severe intraventricular hemorrhage in EPIs. Each is a valuable predictor of adverse outcomes, and their combination demonstrates the highest predictive value, providing significant clinical reference for the early management of these high-risk neonates.